The impact of financial friction on the development and survival of medium-sized enterprises in the Republic of Croatia - Brlečić Valčić, Sonja (Oeconomica Jadertina, 2021)
Financial friction as a link between the return on financial capital, i.e. return on capital and assets, the cost of capital paid by companies, and the amount that investors earn from financial requirements, is rarely used in economic theory and introduced into financial analysis policy, mainly by monetary authorities. Previous research on this topic has indicated the need to introduce such models in financial analysis, mainly for the purpose of examining the need to increase available capital inflows at acceptable rates. This paper proposes a different approach to this problem, i.e. on the sample of financial data for 5 business years of 50 medium-sized Croatian companies, using models based on ANFIS, the impact of financial friction on the development potential of companies has been analysed. In the definition of the model, the variables such as return on assets (ROA), return on equity (ROE), equity ratio, indebtedness ratio and EBITDA margin were used. The conducted analysis can serve entrepreneurs in finding the optimal ratio of financial leverage for sustainable business focused on development strategies, but also policy makers in defining the need to subsidize interest rates on business loans.
Keywords: financial friction; medium enterprise development strategy; sustainable business models